Spreadsheet Programming Design for Wood Connection Calculations In Wood Structure Course - Prayitno, Maria Noorverani; Anisah; Maulana, Arris; Ramadhan, M. Agphin (EDUPEDIA Publisher, 2023)
This study aims to design a spreadsheet programming product for wood connection calculation in wood structure course. This research uses Research and Development (R&D) methods with stages of Define, Design, and Develop. The research instrument used is a questionnaire for product validation by subject expert and media expert. Data analysis of expert validation results was carried out quantitatively-descriptively. The result of this study is a spreadsheet programming product for the calculation of wooden connections called TUSAYU. The validation results show that the resulting spreadsheet programming is eligible for use with an average score percentage of 79.6% (Feasible) in term of subject and 82.8% (Very Feasible) in terms of media.